EVALUASI JALAN LAYANG NON TOL PAKET CASABLANCA KUNINGAN-JAKARTA - Alan Elang Filtrana; Ester Melina; Sri Tudjono; Ilham Nurhuda (Jurnal Karya Teknik Sipil, 2013)
Separated Highway Casablanca Package is located at Kuningan, Jakarta. This separated highways is designed using prestressed concrete box girder construction. The method of execution isused by balance cantilever with precast box girder. The tools is used in the work of box girder is launcher gantry. Total spans on the separated highways are 1175 m, which is divided into 24 spans. This separated highways has seven piers. Design of this package began of planning do the pre-dimension on top of the structure and dimensional on this separated highways have the same dimensions. The next stage is analyzing loads incurred. Load analysis is used, the weight of its own, additional dead load, traffic load, wind load, and earthquake load. From the results of this analysis is then performed structural analysis with the program SAP2000. From the analysis of the structure be able to calculated loss of prestressing force, needs of tendon, and reinforcement of box girder. After that, then do the below structural design by the initial step planning a dimension of the pier. In pier use reinforcement ratio is 1,33 times of minimum reinforcement required by analysis. The final stage in the planning of this package is foundation of pier calculations. Calculation bore pile using Broms method for calculating moments received by the bore pile. Results from these calculations obtained bore pile reinforcement ratio is 0,75%.